ECONOMIC GROWTH AND ITS FACTORS TODAY - Xolbekov Sayfulmalik Eshonqul o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
Today, the basis of all developed countries is the population that is active in economic processes and able to properly fight against economic factors. Therefore, it is necessary for every citizen to have some economic knowledge.